The first case of myxoinflammatory fibroblastic sarcoma affecting the maxillary bone - Boran, Çetin; Kilitci, Asuman; Ahsen, Hilal; Yılmaz, Fahri (International Journal of Health Sciences, 2022)
Myxoinflammatory fibroblastic sarcoma (MIFS) is rare and malignant soft-tissue neoplasms that typically present in the extremities. In the literature, MIFS has been reported in the groin, back, neck, nose, and temporal regions in addition to the extremities. We report a case of MIFS presenting with the complaints of nasal bleeding, purulent nasal discharge, and swelling on the right side of his face. Polypoid tissues protruded from the middle meatus were observed and initial diagnosis was inverted papilloma. The painless tumor was initially mistaken for low-grade myxofibrosarcoma in biopsy. Maxillectomy was performed and made the rare diagnosis of MIFS. Fibroblastic proliferation with extensive local spread from subcutaneous tissue to the epithelium of the maxillary sinus mucosa, maxillary bone, and especially along the bone marrow was observed. To the best of our knowledge, this is the first reported case of MIFS involving the maxillary bone.